Prepričanja in implementacija na dokazih podprte prakse med visokošolsko izobraženimi medicinskimi sestrami in zdravstveniki (2. del) - Skela-Savič, Brigita (Obzornik zdravstvene nege, 2022)
Introduction: Nursing professionals are still not sufficiently empowered to use evidence-based practice competences. The aim of the study was to identify the factors shaping the beliefs on and implementation of evidence-based practice among nurses working in the Slovenian health care system. Methods: This study used a cross-sectional research design. A total of 1,014 nurses with a higher education degree from all three levels of the health care system participated in the study. Two scales were used: EBP Beliefs Scale and EBP Implementation Scale. Data were processed using descriptive, exploratory, and explanatory methods. Results: Overall, a total of 325 participants (38.8%) had received education and training in research, compared to 280 of those (34%) who had received education and training in evidence-based practice. Self-assessed knowledge about research and evidence-based practice was highest among respondents with a master’s degree. Beliefs about evidence-based practice were explained by self-assessed knowledge of evidence-based practice (ß = 0,249) and research (ß = 0,162), total years of employment (ß = ?0,124), job satisfaction (ß = 0,117), training in evidence-based practice (ß = 0,092), and master's degree (ß = 0,077). Implementation of evidencebased practice is explained by beliefs regarding evidence-based practice (ß = 0,306) and employment at a community health centre (ß = 0,132). Discussion and conclusion: Lack of knowledge in research and evidence-based practice and the importance of knowledge obtained through master's programmes are central to developing beliefs regarding evidencebased practice and improving its implementation. Career development at the primary level focused on taking on new roles and linked to both postgraduate education and independent work in nursing proved to be an important factor in the implementation of evidence-based practice.
Keywords: advanced nursing; career development; education; healthcare management; healthcare policy; izobraževanje; karierni razvoj; knowledge; napredna zdravstvena nega; raziskovanje; research; zdravstvena politika; zdravstveni menedžment; znanje